Respuesta :

Answer:

3x - y = -1

Step-by-step explanation:

Standard form of equation is Ax + By = C

y - y1 = m (x -x1)

y - 7 = 3 (x - 2)

y - 7 = 3x - 6

3x - y = -7 +6

3x - y = -1

Answer:  [tex]y-3x=1[/tex]

Step-by-step explanation:

Standard form :

Ax+By=C

We have a linear function y=kx+b ;

we also know its slope k=3 ; and that it passes through the point (2 ; 7 )

Then:

[tex]y=3x+1[/tex]

now substitute the knowledge of the coordinates of the point

[tex]3\cdot 2+b=7 \\\\ b=7-6\\\\ \underline{b=1\ \ \ \ \ }[/tex]

Then we get the function:

[tex]y=3x+1[/tex]

Standard form :

[tex]y-3x=1[/tex]

Ver imagen kamilmatematik100504